Phytochemical Investigation and Biological Activities of Desmodium heterocarpon Extract as Anti-Tyrosinase: Isolation of Natural Compounds, In Vitro and In Silico Study - Suthinee Sangkanu; Wanlapa Nuankaew; Thanet Pitakbut; Sukanya Dej-adisai (Life)
Tyrosinase is an important enzyme in the biosynthesis of melanin. Many skin-whitening agents that inhibit tyrosinase activity from natural sources have been identified because they are harmless and non-toxic. In this work, 114 samples of 54 Fabaceae plants were assessed for their anti-tyrosinase activity using a dopachrome method. The results found that Desmodium heterocarpon stems and roots demonstrated the highest tyrosinase inhibitory activity at 20 µg/mL (92.50 ± 1.09%), whereas the water extract of Artocarpus lacucha and kojic acid demonstrated 87.41 ± 0.61% and 95.71 ± 0.33%, respectively. Six compounds were isolated from this plant, including genistein (1); hexadecanoic acid (2); salicylic acid (3); β-sitosterol-D-glucoside (4); 2,3-dihydroxybenzoic acid (5); and 2,5-dihydroxybenzoic acid (6). Among them, 2,5-dihydroxybenzoic acid demonstrated a potential effect for tyrosinase inhibition with an IC50 of 57.38 µg/mL, while standards of kojic acid and the water extract of A. lacucha showed 2.46 and 0.15 µg/mL, respectively. 2,3-dihydroxybenzoic acid had a similar structure as 2,5-dihydroxybenzoic acid; however, it was shown to have tyrosinase inhibitory activity, with an IC50 of 128.89 µg/mL. Studies using computer simulations confirmed this reservation. The determination of antimicrobial activities found that 2,5-dihydroxybenzoic acid showed the strongest inhibitory activity against Staphylococcus aureus, with MIC and MBC of 5 and 5 µg/mL, respectively. In addition, it inhibited MRSA, S. epidermidis, Propionibacterium acnes, Escherichia coli, and Pseudomonas aeruginosa, with MIC and MBC of 15–30 and 15–40 µg/mL. It showed potential activities against yeast and filamentous fungi, such as Candida albicans, Microsporum gypseum, Trichophyton rubrum, and T. mentagrophytes, with MIC and MFC of 15 µg/mL. So, 2,5-dihydroxybenzoic acid could inhibit tyrosinase activity and microorganisms that cause skin diseases. Therefore, it can be concluded that this plant has advantageous properties that will be investigated and further developed for possible uses, particularly in the cosmetic and pharmaceutical industries.